Integrasi ANP dan TOPSIS dalam Pemilihan Strategi Pemasaran yang Optimal - Gilang Fatikhul Burhan; Christian Soolany (IPB University, 2022)
Creating a competitive advantage by providing value to customers has become a major focus in the formulation of marketing strategies. Making a good marketing strategy, companies can maximize the company's internal strengths and minimize existing weaknesses. CV ABC is a company engaged in the manufacture and supply of agricultural machinery, plantation machinery, fishery machinery, food processing tools and machinery and laboratory equipment. This research process uses the multi-criteria decision-making method Analytic Network Process (ANP) to determine the weight of the importance of the marketing resource evaluation criteria, as well as the TOPSIS method to obtain the best and ideal marketing strategy. The purpose of this research is to determine the optimal marketing strategy to be applied to the company. Therefore, this study uses the ANP method to obtain the relative weight of each criterion based on the respondents' subjective assessment of the company in CV ABC. To assess each marketing strategy, the TOPSIS method is used to rank the best and most ideal marketing strategies applied in the company. Based on the ANP results obtained, there are five criteria that are considered important in determining marketing strategies, these criteria are the ability to relate to customers (0,423), Reputation and Competition (0,208), Human Resource Assets (0,142), Market Innovation Ability (0,140), and Managerial Ability (0,088). The results of the ranking show that the differentiation strategy is the optimal marketing strategy for CV ABC.